Description of the tadpoles of Telmatobius platycephalus and Telmatobius pinguiculus (Anura: Ceratophryidae) from Argentina - Barrionuevo, Jose Sebastian (2009)
The tadpoles of two species of the genus Telmatobius (T. platycephalus and T. pinguiculus) from montane regions of Argentina are described. The larvae of both species are characterized by bodies that are oval in dorsal view and depressed in lateral aspect. In each, the snout is rounded in dorsal and lateral profiles; the labial tooth row formula is 2(2)/3(1) and a short, sinistral spiracle is directed posterodorsally. The tadpoles of T. platycephalus are larger than those of T. pinguiculus; they also lack a row of mental submarginal papillae and the nares are dorsally oriented instead of dorsolaterally.